2019
DOI: 10.3390/cancers11070891
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Extracellular Vesicle-Associated exRNA as Cancer Biomarker

Abstract: Extracellular vesicles (EVs) secreted in biological fluids contain several transcripts of the cell of origin, which may modify the functions and phenotype of proximal and distant cells. Cancer-derived EVs may promote a favorable microenvironment for cancer growth and invasion by acting on stroma and endothelial cells and may favor metastasis formation. The transcripts contained in cancer EVs may be exploited as biomarkers. Protein and extracellular RNA (exRNA) profiling in patient bio-fluids, such as blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 185 publications
(214 reference statements)
0
37
0
Order By: Relevance
“…Blood plasma has now overtaken serum-containing medium as the second most-used source of EVs [12]. Another biofluid, saliva, was not registered in the previous survey but is now studied by 6% of respondents, in line with recent indications of its versatility in biomarker applications [13,14]. Overall, the growing number of researchers sourcing EVs from biofluids relative to cell culture suggests a shift of the EV field towards more in vivo studies and clinical assays.…”
Section: Conclusion and Final Remarksmentioning
confidence: 97%
“…Blood plasma has now overtaken serum-containing medium as the second most-used source of EVs [12]. Another biofluid, saliva, was not registered in the previous survey but is now studied by 6% of respondents, in line with recent indications of its versatility in biomarker applications [13,14]. Overall, the growing number of researchers sourcing EVs from biofluids relative to cell culture suggests a shift of the EV field towards more in vivo studies and clinical assays.…”
Section: Conclusion and Final Remarksmentioning
confidence: 97%
“…Interest in the application of saliva-Exos as potential diagnostic and prognostic biomarkers of cancer is increasing [15]. Few studies have, however, focused on the therapeutic effects of saliva-Exos.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the application of saliva-Exos as potential diagnostic and prognostic biomarkers of cancer is increasing. [15] Few studies have, however, focused on the therapeutic effects of saliva-Exos. The present study demonstrated that treatment of C57/BL6 mice with saliva-Exos promotes wound healing.…”
Section: Discussionmentioning
confidence: 99%